Fatigue resistance of rotary endodontic files subjected to planar and non-planar curvatures induced by in vitro tooth canals. Issue 6 (4th December 2017) - Martins, Rui F.; Fernandes, Alexandre; Lóios, Gonçalo; Ginjeira, António
Abstract : Purpose: The purpose of this paper is to assess the fatigue life of different sizes of HyFlex CM™ endodontic files when submitted to planar or to non-planar curvatures, and to two different rotational speeds, namely 500 rpm or 250 rpm. The influence of superimposing back and forth motion to rotational bending of endodontic files was also assessed. Design/methodology/approach: In all, 64 HyFlex CM™ files of different sizes, namely ref. 0.04/20, 0.06/20, 0.04/35 and 0.06/35, were submitted to rotational bending tests at two different rotational speeds. The planar radius of curvature imposed to the endodontic files was about 4.5 mm, along an angle of 45°, in order to simulate an apical canal that would induce severe loading to the files during clinical treatment. Additionally, 11 Hyflex CM™ files ref. 0.04/20 were submitted to rotational bending tests at 500 rpm inside a mandible first molar manufactured through selective laser melting (SLM), aiming to simulate non-planar curvatures of a real tooth canal. Findings: When considering planar curvature, the endodontic file ref. 0.06/20, tested at 250 rpm, has shown the highest fatigue resistance (4, 185 revolutions, 1, 004 seconds), while the lowest fatigue resistance was registered for instrument ref. 0.04/35 submitted to 500 rpm (747 revolutions, 89 seconds). Hence, depending on the rotational speed, surface finish and the size of the endodontic files tested (taper and tip's diameter), significant differences in fatigue resistance were noticed. If non-planar curvatures were considered, the minimum fatigue resistance was equal to 107 seconds, and back and forth motion allowed extending the minimum fatigue lifetime to 140 seconds. Originality/value: The fatigue resistance of endodontic files is frequently determined through in vitro fatigue tests carried out under single planar curvature or eventually under double planar curvatures. However, non-planar loadings are frequently induced on endodontic instruments when treating root canals with severe multiplanar curvatures. In the research herein presented, a mandible first molar was 3D printed by using the SLM technique in an AISI 316 L stainless steel and more realistic experimental fatigue tests were carried out.